Reimagining Islamic Education in the Age of Artificial Intelligence: Towards a Human-Centered Learning Framework - Najeeb Yahya; Mohammad Ahmad Bani Amer; Markhabat Bolat; Muhammad Eissawy Abu El Yazid; Ahmad Faizal Syahrul Azmi; Ahmad Fauzan Akbar (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study aims to examine how Islamic education can be reimagined in the age of AI through a human-centered learning framework that integrates technological innovation with Islamic educational values. The study employed a qualitative library research approach by systematically reviewing and synthesizing scholarly literature on Artificial Intelligence in Education, Human-Centered Learning, Islamic Educational Philosophy, Human-AI Collaboration, and AI Ethics. Data were collected from peer-reviewed journal articles, academic books, policy reports, and international guidelines published between 2021 and 2026 and analyzed using thematic content analysis. The findings indicate that AI has significant potential to enhance personalized learning, expand educational accessibility, improve instructional effectiveness, and support pedagogical innovation in Islamic educational institutions. However, the integration of AI also raises important concerns related to intellectual dependency, ethical governance, privacy, algorithmic bias, and the preservation of meaningful teacher–student relationships. The study further reveals that Islamic educational concepts such as tarbiyah, ta‘lim, ta’dib, and the framework of Maqāṣid al-Sharīʿah provide a strong ethical and philosophical foundation for guiding responsible AI adoption. The novelty of this study lies in the development of a Human-Centered Learning Framework for Islamic Education that integrates Human-Centered Learning Theory, Artificial Intelligence in Education, Human-AI Collaboration, Islamic Educational Philosophy, and Maqāṣid al-Sharīʿah into a unified conceptual model. The study concludes that AI should function as an augmentative educational partner that supports, rather than replaces, the intellectual, moral, and spiritual roles of educators in fostering holistic human development